Morbidity and mortality of elderly patients following cytoreductive surgery and Hyperthermic Intraperitoneal Chemotherapy (HIPEC). Issue 2 (11th July 2017) - Wong, Evelyn Y.T.; Tan, Grace H.C.; Chia, Claramae S.L.; Kumar, Mrinal; Soo, Khee Chee; Teo, Melissa C.C.
Abstract: Aim: Cytoreductive surgery (CRS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) is known to improve survival in selected patients with peritoneal metastasis. However, there is limited data supporting the role of CRS and HIPEC in elderly patients (≥65 years old). Methods: A retrospective review of a prospectively maintained database of patients who underwent CRS‐HIPEC between April 2001 and July 2015 from a single institution was performed. Patients were divided into two groups non‐elderly (<65 years old), and elderly (≥65 years old). Clinico‐ pathological parameters, morbidity and overall (OS) and disease‐free survival (DFS) of the patients were compared. Results: A total of 177 patients (median age 52, range 9–74) underwent CRS‐HIPEC with curative intent. There were 159 non‐elderly patients and 18 elderly patients. Median PCI scores were 12 (0–39) for the non‐ elderly patients and 11 (1–29) for the elderly patients ( p =0.77). High‐grade complications occurred in 39 non‐elderly patients (24.5%) and 8 elderly patients (44.4%) ( p =0.79), while 58 non‐elderly patients (38.7%) and 7 elderly patients (41.2%) stayed in ICU for more than 1 day ( p =0.69). There was no difference in the 30‐day mortality between the two groups (0% vs. 0%, p =1). After a median follow‐up of 16 months for all patients, there was no difference in 5‐years OS (51.0% vs. 59.6%, p =0.88) and 5‐years DFS (23.3% vs. 53.3%, p =0.60) between non‐elderly and elderly patients. Conclusions: Surgical outcomes after CRS‐HIPEC do not differ significantly between non‐elderly and elderly patients. Hence, age should not be a contraindication in selecting patients for CRS and HIPEC.